CORN SEED UNDER SOIL COMPRESSION AND DEEP SEEDLING: INFLUENCE ON THE EMERGENCE SPEED INDEX - PRADO, Renato de Mello; TORRES, José Luís; ROQUE, Cassiano Garcia; COAN, Osvaldo (Scientia Agraria, 2001)
The levels of soil depth and soil compactation on the seed affecting the seedlings speed emergence, consequently, the initial maize plants stablishment. With the objective to study the influence of sowing depth and soil compactation on the seed of a initial established maize crop, an experiment was conducted at the Faculdade de Ciências Agrárias e Veterinárias / UNESP, Jaboticabal, SP, from April to June, 1999, in haplustox. A completely randomized desing was used with three replications. The treatments of the soil compactation in four levels: 0 (control), 5, 10 and 15 kgf corresponding to a resistence to penetration of 1.91, 3.39, 3.93 and 4.43 Mpa, respectively, and depths sowed in three levels: 3, 5 and 7 cm. Emergence speed rate (ESR) and plant height were evaluated weekly during the first 60 days. The results showed that to initial established maize plants the answers were linear form to emergence speed rate and the plant height to a soil compactation varied betwen 5 to 15 kgf achieved by compacting wheel, no restriction at a sowing depth of 3 to 7 cm.